Characterisation of HV-MAPS ATLASPix3 and its applications for future lepton colliders. (1st September 2022) - Raciti, B.; Gao, Y.; Schimassek, R.; Andreazza, A.; Feng, Z.; Fox, H.; Han, Y.; Li, Y.; Martin, J.; Peric, I.; Sabatini, F.; Velthuis, J.; et al.
Abstract: HV-MAPS are a novel type of CMOS depleted active pixel sensors for ionizing particles, implemented in standard CMOS processes, that have been proposed in several future particle physics experiments for particle tracking. In depleted monolithic sensors, the sensor element is the n-well/p-substrate diode. The sensor matrix and the readout are integrated in one single piece of silicon and the electronics is embedded in shallow wells inside deep n-wells, isolated from the substrate. High voltage biasing increases the depth of the depletion region, improving sensor properties as signal amplitude, charge collection speed and radiation tolerance. ATLASPix3 is the first full reticle size high voltage Monolithic Active Pixel CMOS sensor, designed to meet the specifications of the outer layers of the ATLAS inner tracker (ITk). Its thin design, the excellent position resolution, high readout rate and high radiation tolerance make ATLASPix3 an ideal candidate for large-area tracking detector R&D of future collider experiments such as the Circular Electron Positron Collider (CEPC) silicon tracker.